Burch colposuspension performed at cesarean delivery in pregnancies complicated by genuine stress urinary incontinence - Sapmaz, E; Çelik, H (Sci Printers & Publ Inc, 2003)
OBJECTIVE: To investigate the efficiency and reliability of performing Burch colposuspension at the time of cesarean delivery for genuine stress urinary incontinence diagnosed before pregnancy. STUDY DESIGN: Eight women diagnosed with genuine stress urinary incontinence before pregnancy were included in this prospective, descriptive study. They underwent Burch colposuspension at the time of elective cesarean delivery. Sociodemographic characteristics of the patients, total operation time, intraoperative blood loss, amount of fluid flowing from the hemovac drain in the space of Retzius, postoperative analgesic need and length of hospitalization were recorded. Patients were reevaluated on postoperative week 6, as well as at 6 and 12 months. The descriptive statistics of the patients were performed using the SPSS 9.0 statistical program (SPSS, Chicago, Illinois). RESULTS: Total operation time was 37 +/- 7 minutes, average intraoperative blood loss was 345 +/- 23 mL, amount of serosanguineous fluid flowing from the hemovac drain placed in the space of Retzius was 31 +/- 3.6 mL, and the length hospitalization was 5 0 days. None of the patients needed additional analgesics during the postoperative period. No intraoperative or postoperative complications occurred. When the patients were evaluated during follow-up, they had no symptoms of incontinence. The cotton-tipped-swab and stress test findings were normal. CONCLUSION: The results of this pilot study indicate that Burch colposuspension performed at the time of cesarean delivery for genuine stress urinary incontinence diagnosed before pregnancy is effective and reliable.
Keywords: urinary incontinence, stress; cesarean section; Burch colposuspension